Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1177/0033294116657586
|View full text |Cite
|
Sign up to set email alerts
|

Examining Competing Models of Transformational Leadership, Leadership Trust, Change Commitment, and Job Satisfaction

Abstract: This study discusses the influence of transformational leadership on job satisfaction through assessing six alternative models related to the mediators of leadership trust and change commitment utilizing a data sample (N = 341; M age = 32.5 year, SD = 5.2) for service promotion personnel in Taiwan. The bootstrap sampling technique was used to select the better fitting model. The tool of hierarchical nested model analysis was applied, along with the approaches of bootstrapping mediation, PRODCLIN2, and structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 29 publications
0
15
0
2
Order By: Relevance
“…Similarly, the relationship between transformational leadership and trust was also found to be significant in Browning's (2014) study of heads of schools in Australia. From a private-sector perspective, Waziri, Ali, and Aliagha (2015) found that transformational leadership is positively related to the adoption of information and communication technology in the construction industry in Nigeria, Yang (2016) found that transformational leadership engendered trust and commitment to change in the insurance sector in Taiwan whilst Babić, Savović, and Domanović (2014) found that transformational leadership is positively related to attitudes toward change in Serbian firms. Yasir et al (2016) found that trust in the leader mediates the relationship between transformational leadership and organisational change capacity in the not-for-profit sector in…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the relationship between transformational leadership and trust was also found to be significant in Browning's (2014) study of heads of schools in Australia. From a private-sector perspective, Waziri, Ali, and Aliagha (2015) found that transformational leadership is positively related to the adoption of information and communication technology in the construction industry in Nigeria, Yang (2016) found that transformational leadership engendered trust and commitment to change in the insurance sector in Taiwan whilst Babić, Savović, and Domanović (2014) found that transformational leadership is positively related to attitudes toward change in Serbian firms. Yasir et al (2016) found that trust in the leader mediates the relationship between transformational leadership and organisational change capacity in the not-for-profit sector in…”
Section: Discussionmentioning
confidence: 99%
“…Job satisfaction is one of the most analyzed attitudes in the organizational behavior field and is defined as the degree to which the individual positively evaluates his or her job experiences (Yang, 2016). It is considered to be a particularly important factor because, when missing, it is associated with undesired outcomes in the work environment, such as voluntary turnover, absenteeism, and occupational illness.…”
Section: Effects Of Leadership On Job Satisfaction: Contextual Factorsmentioning
confidence: 99%
“…Transformational leaders serve as an inspiration to their followers by engaging in effective communication that encourages trust, commitment, and consequently greater satisfaction. Based on this premise, many researchers have dedicated themselves to empirically examining the relationship between transformational leadership and job satisfaction (Riaz & Haider, 2010;Yang, 2016). In a quantitative literature review based on studies from 1994 to 2004, Judge and Piccolo (2004) noticed a strong association between transformational leadership and job satisfaction.…”
Section: Effects Of Leadership On Job Satisfaction: Contextual Factorsmentioning
confidence: 99%
“…Individuals with commitment to change would feel attached and strive to make the change a success (Herscovitch & Meyer, 2002). Previous research proved that com-mitment to change could increase behavioural support for change and creative behaviour for change (Seo, Taylor, Hill, Zhang, Tesluk, & Lorinkova, 2012); implementation of innovation (Michaelis, Stegmaier, & Sonntag, 2010); voicing concerns about change (Cinite & Duxbury, 2018); job satisfaction (Yang, 2016) and reduce resistant behaviour towards change (Seo et al, 2012); and turnover intention (Cunningham, 2006;Shin, Seo, Shapiro, & Taylor, 2015).…”
Section: Introductionmentioning
confidence: 99%